2005
DOI: 10.1159/000086306
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Number of Infective Trichinella spiralis Larvae in Mice by Use of Homeopathic Drugs

Abstract: Background: Trichinellosis caused by the gastrointestinal nematode Trichinella spiralis occurs in humans, domestic animals and wild animals. It is difficult to control the muscle phase of the parasite. Homeopathic drugs such as Cina and Santoninum have anthelmintic properties. We have observed that in material doses, the homeopathic drug Podophyllum also has nematotoxic properties. We have also observed that homeopathic potency can influence the water permeability of cells. Objective: The purpose of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, the detailed mechanisms of these influences remain unclear. In another related study, Sukul et al (2005) studied the effects of potentized homeopathic drugs, Cina 30 (obtained from Artemisia nilagirica), Santoninum 30 and Podophyllum mother tincture (prepared from Podophyllum hexandrum) on muscle phase of the parasite T. spiralis in mice and observed that potentized drugs such as Cina 30 and Santoninum 30 were more effective (84.10% and 81.20%, respectively) in reducing the larval population in the muscles of mice than the crude extract of Podophyllum (68.14%). It thus appears from these studies that different plant extracts and/or their products vary in their effectiveness to different stages of T. spiralis but by and large, their efficacy appears to be comparatively low against the encysted larvae of parasite.…”
Section: Resultsmentioning
confidence: 91%
“…However, the detailed mechanisms of these influences remain unclear. In another related study, Sukul et al (2005) studied the effects of potentized homeopathic drugs, Cina 30 (obtained from Artemisia nilagirica), Santoninum 30 and Podophyllum mother tincture (prepared from Podophyllum hexandrum) on muscle phase of the parasite T. spiralis in mice and observed that potentized drugs such as Cina 30 and Santoninum 30 were more effective (84.10% and 81.20%, respectively) in reducing the larval population in the muscles of mice than the crude extract of Podophyllum (68.14%). It thus appears from these studies that different plant extracts and/or their products vary in their effectiveness to different stages of T. spiralis but by and large, their efficacy appears to be comparatively low against the encysted larvae of parasite.…”
Section: Resultsmentioning
confidence: 91%
“…Cina 30c and Santoninum 30c were effective in reduction of Trichinella spiralis larvae infection in muscle tissue. 60 Lira-Salazar and co-workers, demonstrated the effect of Eupatorium perfoliatum 30cH and Arsenicum album 30cH on Plasmodium berghei infected mice. 13 In both cases parasite multiplication was inhibited, but the most interesting observation was the increase in the number of schizonts (the Plasmodium parasite form found inside the red blood cells), suggesting an interruption of Plasmodium life cycle in this intracellular phase.…”
Section: Conceptual Aspectsmentioning
confidence: 99%
“…[ 17 , 18 , 19 , 20 ]] Due to the limitations in the present study and the fact that the number of tachyzoites should have been the same in all intraperitioeal injections to the laboratory mice, the number of tachyzoites injected to each mouse was 2×10 3 , which has been greatly higher than the "Lowest" Lethal Dose; LD100. ]] Due to the limitations in the present study, and considering the importance of the expedient equality of the number of the injected bacteria to the mice, the amount of the intraperitioeally-injected bacteria was 2×10 5 , which was much less than the "Lowest" Lethal Dose; LD 100 .…”
Section: Infectious Organisms and Challenge Mannermentioning
confidence: 73%